A preliminary physical-chemical analysis of steam reforming of biogas from a small wastewater treatment system of a University Campus - Souza, Antonio Carlos Caetano [UNESP]; Silveira Sr., José Luz [UNESP]; Silva, Marcio Evaristo [UNESP]; Corghi, Manuela [UNESP] (My University, 2008)
The need to reduce environmental impact caused by energy generation and consumption has led researches concerning renewable resources such as biogas. A small wastewater treatment system with biogas production was developed in São Paulo State University, campus of Guaratinguetá, Brazil. A project was approved under support by FAPESP, a state-owned company responsible by financial support of projects performed in the Brazilian state of São Paulo. A theoretical analysis was developed to evaluate the content of hydrogen to be produced through steam reforming. The content of filtered and dried biogas produced in this wastewater treatment system was 80% CH4 and 20% CO2. At 1 atm, the predicted content of the gases in the synthesis gas was 57% H2 at 300°C and 58% H2 at 800°C, where the reaction could be terminated. At this temperature, 27% CO2, 9% CO, 6% solid carbon, and small traces of ethylene and acetylene could be encountered. This is an abstract of a paper presented at the 2008 AIChE Spring National Meeting (New Orleans, LA 4/6-10/2008).